The context of REDD+ in Indonesia: Drivers, agents and institutions [Update edition] - Dwisatrio, B.; Said, Z.; Permatasari, A.P.; Maharani, C.; Moeliono, M.; Wijaya, A.; Lestari, A.A.; Yuwono, J.; Pham Thu Thuy (Center for International Forestry Research, 2021)
This country profile is a second version from the first country profile that was published by CIFOR in 2012. Since then, REDD+ developments has changed drastically in Indonesia. This version documents changes from 2012 to 2020, on drivers of deforestation and forest degradation, institutional settings and governance for REDD+, the political economy of drivers of deforestation and forest degradation, REDD+ actors and 3Es (Effectiveness, Efficiency and Equity) implementation. Indonesia keeps the commitment to addressing climate change but reducing deforestation and forest degradation remains a challenge. Major issues surrounding REDD+ implementation include weak implementation of various international agreements, contradictory regulations and weak coordination between government agencies, changing national political regimes that affects transformation commitment, disconnection between central and regional levels, unclear REDD+ projects impact, and continuous business as usual solution to bridge conservation and development. More attention to elite capture is needed to avoid bias of promoting business and economic growth for the benefit of all but at the expense of the environment.